The Discourse on Sexuality in Islamic Bioethics Perspective Ingrid Mattson - Umam, Miftahul; Al Jufri, Muhammad Arman; Rohmaniyah, Inayah (Graduate School of UIN Syarif Hidayatullah Jakarta, 2022)
Recently, the issue of sexuality in Islamic bioethics has often led to discrimination on gender issues, especially against women. The model for reading religious texts influenced by patriarchal culture and the massive development of health technology are allegedly the two reasons for this problem. This article examines sexuality in the discourse of Islamic bioethics developed by Ingrid Mattson. This article is included in qualitative research with the type of literature study. The discourse on sexuality in Islamic bioethics developed by Ingrid Mattson is a material object in this research. At the same time, the formal object of this research is discourse theory. The three points described in this study include; what is the form of discourse reading religious texts about sexuality in Islamic bioethics from the perspective of Ingrid Mattson, what are the background factors, and what are the implications. As a result, Ingrid Mattson's reading of religious texts must present the historicity of each verse and consider a gender balance. The factor that causes this discourse to exist is discrimination, verses that defend women in sexuality. This discourse's implications can unravel the discrimination problem that often befalls women and children.